2013
DOI: 10.1177/0300985813511125
|View full text |Cite
|
Sign up to set email alerts
|

Histologic Characterization of the Cat Middle Ear

Abstract: The purpose of this study was to establish microscopic normal in the middle ear of the cat while concurrently characterizing gross and microscopic lesions reflecting spontaneous otitis media. Both ears from 50 cats were examined grossly and processed for histologic examination of the external, middle, and internal ear on a single slide. Gross lesions of the middle ear were present in 14 of 100 (14%) and included turbid fluid, frank pus, hemorrhage, and fibrous thickening of the auricular mucoperiosteum. Histol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 16 publications
1
31
1
Order By: Relevance
“…Moreover, their variable number, size, and shape could suggest different stages of bony proliferation of the TB in response to injury. 8,12 Sula et al 12 reported an active inflammatory infiltrate as well as extensive fibrosis of the auricular mucoperiosteum with or without bony proliferation, lysis, or remodeling in cats with chronic otitis media. Unfortunately, in the series of 8 lion skulls, the skeletonized condition of the samples restricted our histologic findings to the bone lesions but should encourage further investigations in postmortem studies of large felines.…”
Section: Microscopic Findingsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, their variable number, size, and shape could suggest different stages of bony proliferation of the TB in response to injury. 8,12 Sula et al 12 reported an active inflammatory infiltrate as well as extensive fibrosis of the auricular mucoperiosteum with or without bony proliferation, lysis, or remodeling in cats with chronic otitis media. Unfortunately, in the series of 8 lion skulls, the skeletonized condition of the samples restricted our histologic findings to the bone lesions but should encourage further investigations in postmortem studies of large felines.…”
Section: Microscopic Findingsmentioning
confidence: 99%
“…Infectious (bacterial) otitis media has been more frequently described in dogs, cats, and cows. 7,12,13 Sula et al 12 recently described the histologic characteristics of diseased ears in a series of 50 cats and concluded that middle ear diseases in cats are far more common than gross lesions or clinical literature suggests.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that osteoneogenesis, formation of new bone, is also occurring during chronic middle ear infection as pointed by [12]. Such bone formation could result in the appearance of spicule pointing normal to the bone septae, as also illustrated in [75]. Fig.…”
Section: Bone Spiculesmentioning
confidence: 89%
“…Though cats have a bulla instead of a mastoid as in humans, Sula et al [75] reported the occasional formation of irregular bony spicules in cats with a history of chronically affected ears . Per Cayé-Thomasen et al [11] reported the formation of bone in the presence of a pathological bone, such as in chronic otitis media.…”
Section: Bone Spiculesmentioning
confidence: 99%